2023
DOI: 10.1039/d2gc03160d
|View full text |Cite
|
Sign up to set email alerts
|

Emerging carbon-based quantum dots for sustainable photocatalysis

Abstract: Carbon-based quantum dots (QDs), as a new type of zero-dimensional (0D) inorganic material, have been favored by researchers, since their superior optical properties, good water solubility and biocompatibility. Besides graphene...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 155 publications
(291 reference statements)
1
26
0
Order By: Relevance
“…Compared with Cd treatment alone, the application of CDs alleviated the life inhibition and photosynthetic inhibition of Cd stress to a certain extent. Similar research results were found in Rice (Fang, 2020) and melon (Wang et al, 2019).…”
Section: Imaging Cds In Ryegrasssupporting
confidence: 86%
See 1 more Smart Citation
“…Compared with Cd treatment alone, the application of CDs alleviated the life inhibition and photosynthetic inhibition of Cd stress to a certain extent. Similar research results were found in Rice (Fang, 2020) and melon (Wang et al, 2019).…”
Section: Imaging Cds In Ryegrasssupporting
confidence: 86%
“…Studies have shown that CDS can reduce the toxic effect of Cd on citrus by increasing the content of chlorophyll and anthocyanin (Li et al, 2019). The toxicity of Cd on melon seedlings was repaired by alleviating oxidative stress, reducing the inhibition of antioxidant enzyme activity and reducing the accumulation of cadmium in roots and leaves (Wang et al, 2019). All these lay a foundation for carbon quantum dots as a new phytoremediation agent.…”
Section: Introductionmentioning
confidence: 99%
“…4a, ZIF-67 exhibited visible absorption around 250 and 550 nm, which were assigned to ligand-to-metal charge transfer (LMCT) and metal-to-metal (MMCT) charge transfer, respectively. In addition, the peaks at 539, 564, and 585 nm could be attributed to the 4 A 2 (F) → 4 T 1 (P) tetrahedral coordination of cobalt-energy shift in ZIF-67. 47 The strong absorption at 550 nm indicated the possibility of visible-light absorption.…”
Section: Mechanism Of Co(oh) 2 @Zif-67-enhanced Photocatalytic Oxidat...mentioning
confidence: 94%
“…Photocatalytic oxidation has attracted growing attention in water-splitting, organic synthesis, and pollutant degradation due to its easy operation, high efficiency, and minimal secondary pollution. [1][2][3][4] It is one of the most effective ways to decompose volatile organic compounds (VOCs). 5,6 To achieve effective photocatalytic oxidation, an external light source is generally required, which complicates the equipment and limits usage in small operating spaces.…”
Section: Introductionmentioning
confidence: 99%
“…[14] As a new type of zero-dimensional carbon-based fluorescent nanomaterials, carbon dots (CDs) stand out among many fluorescent nanomaterials due to their excellent and unique optical properties, [15] which have a wide range of promising applications and become a hot research topic in recent years. [16] CDs possess the low cost of synthesis, [17,18] good water solubility and biocompatibility, [19] and excellent photoluminescence (PL) properties, [20] which are difficult to achieve by conventional semiconductor quantum dots. Furthermore, CDs possess many functional groups on their surface, such as amino (-NH 2 ), hydroxyl (-OH), and carboxyl groups (-COOH), which are beneficial for CDs to be utilized as fluorescent nanoprobes for detection and analysis.…”
Section: Introductionmentioning
confidence: 99%